Ferulate and lignin cross-links increase in cell walls of wheat grain outer layers during late development. (November 2018) - Chateigner-Boutin, Anne-Laure; Lapierre, Catherine; Alvarado, Camille; Yoshinaga, Arata; Barron, Cécile; Bouchet, Brigitte; Bakan, Bénédicte; Saulnier, Luc; Devaux, Marie-Françoise; Girousse, Christine; Guillon, Fabienne
Highlights: Lignins were detected earlier than previously reported in developing wheat grain. Alkali-releasable ferulate increased during development of grain outer layers. Ferulate and lignin monomers releasable from pericarp decreased at grain maturity. Resistant bonds between cell wall polymers probably form at maturity. Abstract: Important biological, nutritional and technological roles are attributed to cell wall polymers from cereal grains. The composition of cell walls in dry wheat grain has been well studied, however less is known about cell wall deposition and modification in the grain outer layers during grain development. In this study, the composition of cell walls in the outer layers of the wheat grain ( Triticum aestivum Recital cultivar) was investigated during grain development, with a focus on cell wall phenolics. We discovered that lignification of outer layers begins earlier than previously reported and long before the grain reaches its final size. Cell wall feruloylation increased in development. However, in the late stages, the amount of ferulate releasable by mild alkaline hydrolysis was reduced as well as the yield of lignin-derived thioacidolysis monomers. These reductions indicate that new ferulate-mediated cross-linkages of cell wall polymers appeared as well as new resistant interunit bonds in lignins. The formation of these additional linkages more specifically occurred in the outer pericarp. Our results raised the possibility that stiffening of cell walls occur at late development stages in the outer pericarp and might contribute to the restriction of the grain radial growth.